2012
DOI: 10.1063/1.4729077
|View full text |Cite
|
Sign up to set email alerts
|

Excitation wavelength dependent photoluminescence in structurally non-uniform Si/SiGe-island heteroepitxial multilayers

Abstract: In nanometer-size Si/SiGe-island heteroepitxial multilayers grown on Si(001), low temperature photoluminescence spectra are observed that strongly depend on the excitation wavelength and show a strong correlation with structural properties revealed by transmission electron microscopy. These experimental results can be explained by assuming that the optically created carriers are strongly localized at Si/SiGe island heterointerfaces. We show that electron-hole pairs are generated and recombine within spatial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…This process is even more efficient at the Si/Ge hetero-interface, where the $8 nm thick SiGe alloy layer is found. In SiGe alloys and nanostructures, compositional fluctuation is known to be responsible for low-temperature exciton localization; 43 therefore, exciton diffusion toward the surface is suppressed. Also, SiGe compositional fluctuation is responsible for the reduction of the exciton radiative lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…This process is even more efficient at the Si/Ge hetero-interface, where the $8 nm thick SiGe alloy layer is found. In SiGe alloys and nanostructures, compositional fluctuation is known to be responsible for low-temperature exciton localization; 43 therefore, exciton diffusion toward the surface is suppressed. Also, SiGe compositional fluctuation is responsible for the reduction of the exciton radiative lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…At an excitation wavelength of 325 nm with a penetration depth of only ~10 nm, the PL spectrum is shifted slightly toward lower photon energy and has a significantly reduced FWHM (~100 meV). This result demonstrates that the cluster composition and Si/SiGe interface abruptness, as illustrated in Figures 11 and 12, are influencing the PL behavior: the more abrupt the Si/SiGe interface, the smaller the FWHM of the PL peak, and, in the topmost SiGe layer, a higher Ge composition results in the PL peak being shifted toward lower photon energy (Modi et al, 2012a). In other similar samples, it has been shown that continuous optical excitation at shorter wavelengths produces substantial PL fatigue after a delay of about 10 min due to the accumulation of charge within the SiGe clusters (Modi et al, 2012b).…”
Section: Photoluminescence From Sige Nanostructuresmentioning
confidence: 77%
“…Single Nanometer-Thick SiGe Nanocluster Sample A TEM micrograph of a specially fabricated sample containing a very thin Si1−xGex cluster layer above a regular stack of such cluster layers that was grown using Si/SiGe MBE is shown in Figure 10A (Modi et al, 2012a). The sample is grown on a Si substrate and comprises two SiGe cluster layers with a cluster height of ~6-8 nm separated by a Si layer of ~8 nm thickness between the SiGe clusters (i.e., there are two SiGe/Si pairs); a 30-nm-thick Si spacer layer; another five SiGe/Si layer pairs to initiate 3D growth; a layer of SiGe clusters with a height of approximately 18 nm; a thinner separating Si layer; a final SiGe cluster layer; and a thin Si cap.…”
Section: Photoluminescence From Sige Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations